Ultrafast synthesis of L-His-Fe3O4 nanozymes with enhanced peroxidase-like activity for effective antibacterial applications - Yuan, Ye; Liu, Yuan; Shen, Zhipeng; Wu, Huidan; Meng, Lantian; Guo, Xiaoxiao; Jiang, Bing; Fang, Ling (Frontiers in Bioengineering and Biotechnology, 2025)
Background: Bacterial resistance remains a significant challenge, necessitating the development of new antibacterial strategies. This study introduces a rapidly synthesized L‐histidine‐ Fe3O4 (L‐His‐Fe3O4) nanozyme with enhanced peroxidase (POD)‐like activity, designed to improve antibacterial efficacy and accelerate the healing of bacteria-infected wounds.Methods: We successfully synthesized L‐His‐Fe3O4 using an ultrafast, room-temperature synthesis method, and observed its anti-infection effect and explored its anti-infection mechanism through in vivo and in vitro antibacterial experiments.Results: We produced L‐His‐Fe3O4 cost-effectively while preserving L‐His, which was essential for its catalytic and antibacterial functions. The resulting nanozyme demonstrated exceptional antibacterial activity against both Gram-positive (S. aureus) and Gram-negative (E. coli) bacteria. In vivo experiments revealed that L‐His‐Fe3O4 outperformed vancomycin in reducing bacterial viability and effectively promoting wound healing, all while maintaining excellent biosafety with no adverse effects on blood or liver functions.Discussion: These findings highlight the potential of L‐His‐Fe3O4 for large-scale production and practical use in treating bacterial infections, offering a promising approach to combating antibiotic-resistant pathogens.